The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cphc.201701046
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Copper Speciation in the Low Temperature Oxidative Upgrading of Short Chain Alkanes over Cu/ZSM‐5 Catalysts

Abstract: Partial oxidative upgrading of C -C alkanes over Cu/ZSM-5 catalysts prepared by chemical vapour impregnation (CVI) has been studied. The undoped ZSM-5 support is itself able to catalyse selective oxidations, for example, methane to methanol, using mild reaction conditions and the green oxidant H O . Addition of Cu suppresses secondary oxidation reactions, affording methanol selectivities of up to 97 %. Characterisation studies attribute this ability to population of specific Cu sites below the level of total e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Of course, as well as using novel materials, we can consider new ways of making Cu‐based catalysts. One approach, which could be environmentally beneficial is to avoid a solvent in the preparation and we have recently reported data for such a catalyst produced by anti‐solvent methods utilising supercritical CO 2 or gas phase chemical vapour impregnation (CVI) . This produces good catalysts with high dispersion of the Cu, but for efficiency, the former requires excellent recycling of the CO 2 .…”
Section: Novel Catalystsmentioning
confidence: 99%
“…Of course, as well as using novel materials, we can consider new ways of making Cu‐based catalysts. One approach, which could be environmentally beneficial is to avoid a solvent in the preparation and we have recently reported data for such a catalyst produced by anti‐solvent methods utilising supercritical CO 2 or gas phase chemical vapour impregnation (CVI) . This produces good catalysts with high dispersion of the Cu, but for efficiency, the former requires excellent recycling of the CO 2 .…”
Section: Novel Catalystsmentioning
confidence: 99%
“…The oxidation of C 1 -C 3 alkanes utilising H 2 O 2 in conjunction with HZSM-5 [28][29][30][31][32] in addition to AuPd nanoparticles supported on TiO 2 [33,34] at low temperature have been extensively reported, with the valorisation of methane to methanol in particular an attractive option to produce a versatile chemical feedstock. Indeed, we have previously reported that greater selectivity, at comparable catalytic productivity, towards methane can be achieved when generating H 2 O 2 from H 2 and O 2 compared to preformed, commercially synthesised H 2 O 2 [35].…”
Section: Introductionmentioning
confidence: 99%
“…This TOF is still significantly higher than the previously reported results. 34,48,49,75,87,88 Despite the existence of the bottleneck due to the activity-selectivity trade-off, it is still promising to improve DMTM catalysts using H2O2 as the oxidant in the future.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…47 Hutchings and his colleagues found that copper addition in Cu-ZSM-5 can provide up to 97 % CH3OH selectivity in the presence of H2O2 at 50°C. 48 Tang et al reported that Cu1-O4/ZSM-5 single atom catalyst exhibits a 99% selectivity of C1 oxide with high conversion of CH4 at 50 °C. 49 However, H2O2 is likely to readily generate the free radicals of •OH and •OOH as well, thereby possibly triggering a Fenton reaction and reducing the CH3OH selectivity.…”
Section: Introductionmentioning
confidence: 99%